Analysis And Design Of Active Grating-Embedded Optical Filters - Lim , Kian Yong (2005)
The rapid development of optical fibre-based communication, triggered by the ever increasing demand for broadband communication, has paved the way for intensive research in the area of optical devices such as transmitters, receivers, filters and other optical components. The main objective of this theis is to study and model different structures of active wavelength tunable optical filter. Two novel DFB filter structures have been proposed, namely the phase-shift-controlled (PSC) DFB optical filter with distributed coupling coefficient (DCC); and the gain-coupled (GC) phase-shift-controlled DFB structure.